Personality traits and financial outcomes - Claire Greene; Oz Shy; Joanna Stavins (Federal Reserve Bank of Boston, 2023)
The Big Five personality traits-openness to experience, conscientiousness, extroversion, agreeableness, and neuroticism-are widely used in understanding human behavior. Using data collected from a survey and diary of consumer payment choice, we investigate how the Big Five traits affect three financial outcomes: being unbanked, holding a credit card, and carrying credit card debt. Although each personality trait is correlated with each of the financial outcomes we examine, they mostly become statistically insignificant when we control for demographics and income in regressions. Carrying credit card debt (revolving), however, is significantly affected by conscientiousness, openness, and agreeableness: Credit card adopters who are less conscientious, more open to experiences, or more agreeable are significantly more likely to revolve credit card debt. A machine learning algorithm confirms that conscientiousness is the major factor separating revolvers from other credit cardholders.
Keywords: D12; D14; E42; 330; credit card debt; consumer payments; personality traits; financial behavior; unbanked